2018
DOI: 10.1111/ced.13652
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like-2 mutations and reduced mRNA and protein expression in mid-dermal elastolysis

Abstract: Our present data suggest that decreased elastin renewal due to LOXL2 mutations and consecutive reduced LOXL2 expression contribute to the pathogenesis of MDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…This hypothesis thus raises the possibility that LOXL2 participates in some steps of elastogenesis together with other LOXs. The recent identification of patients suffering from middermal elastolysis also supports the direct involvement of LOXL2 in the stability and maintenance of elastin ( 14 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This hypothesis thus raises the possibility that LOXL2 participates in some steps of elastogenesis together with other LOXs. The recent identification of patients suffering from middermal elastolysis also supports the direct involvement of LOXL2 in the stability and maintenance of elastin ( 14 ).…”
Section: Discussionmentioning
confidence: 78%
“…The association of LOXL2 with ELN as a susceptibility gene for glaucoma was already proposed in Urban et al ( 34 ), but no functional interaction between these proteins was demonstrated in this study. More recently, the identification of LOXL2 mutations in patients suffering from middermal elastolysis directly raised the possibility that LOXL2 could participate in elastin cross-linking ( 14 ). We show here the direct binding of LOXL2 to TE using surface plasmon resonance, and we could detect lysine oxidation by recombinant LOXL2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La patogenia de la EDM no está bien comprendida pero se ha demostrado desequilibrio entre la activación exagerada de metaloproteinasas (MMP) de la matriz y una disminución en los inhibidores de elastasa que controlan la actividad catalítica, dando como resultado final pérdida de fibras elásticas 3,8 . Además se encontraron mutaciones en la enzima lisyl oxidasa, responsable de la formación de colágeno y elastina en la matriz extracelular 8,9 . La radiación ultravioleta es un cofactor de activación de MMP y es elevado el porcentaje de pacientes con antecedente de exposición solar previa al desarrollo de lesiones 2 .…”
Section: Comentariounclassified
“…Lysyl oxidase-like 2 (LOXL2) is a member of the lysyl oxidase (LOX) gene family, which plays an important role in development, senescence, tumor suppression, cell growth, and chemotaxis [ 19 ]. LOXL2 catalyzes the oxidative deamination of the peptidyl lysine residues of extracellular matrix (ECM) proteins, such as, collagen and elastin, and promotes cross-linking of the ECM [ 20 , 21 ]. LOXL2 regulates angiogenesis by mediating collagen IV scaffolding [ 22 ].…”
Section: Introductionmentioning
confidence: 99%